1997
DOI: 10.1016/s0014-5793(97)00609-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced oxidizability of ubiquinol and α‐tocopherol during lovastatin treatment

Abstract: A double-blinded, placebo-controlled cross-over trial was carried out with 27 hypercholesterolemic men with coronary heart disease. During the 6-week treatment period lovastatin (60 mg/day) decreased fasting serum LDL cholesterol by 45%, LDL phosphorus by 38% and apoB by 33%. Ubiquinol content diminished by 13% as measured per LDL phosphorus. When LDL was oxidized ex vivo with AMVN both LDL ubiquinol and a-tocopherol were exhausted faster after lovastatin treatment compared to placebo, by 24% (P < 0.005) and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…[27][28][29][30][31][32] Its level may be reduced by high-dose treatment with an HMG-CoA reductase inhibitor. 17,[33][34][35][36] In the present study, the LDL ubiquinol level decreased during the LT period. The lag time to conjugated-diene formation in ex vivo, isolated LDL was prolonged by ␣-tocopherol treatment (450 IU/d), regardless of concomitant treatment with lovastatin or placebo.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…[27][28][29][30][31][32] Its level may be reduced by high-dose treatment with an HMG-CoA reductase inhibitor. 17,[33][34][35][36] In the present study, the LDL ubiquinol level decreased during the LT period. The lag time to conjugated-diene formation in ex vivo, isolated LDL was prolonged by ␣-tocopherol treatment (450 IU/d), regardless of concomitant treatment with lovastatin or placebo.…”
Section: Discussionmentioning
confidence: 70%
“…17,38,40,48 -52 These phenomena may be secondary to a greater decrease in the lipid moiety than that of the proteins in LDL. 17,49,53 Later phases of LDL oxidation can also be studied by using excessive, longlasting oxidation with other measures for LDL peroxidation, like the determination of thiobarbituric acid-reactive substances and trinitrobenzenesulfonic acid, 38 or LDL malondialdehyde, peroxides, and the total amount of conjugated dienes. 54 This kind of long-lasting oxidation may also lead not only to peroxidation of the lipids in the LDL particle but also to the degradation of its protein, like the inner part of apo B.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mohr et al demonstrated that supplementation with CoQ10 resulted in an increased CoQ10 level within circulating human lipoproteins and in an increased resistance of LDL to incipient lipid peroxidation (29). Palomaki et al (30) reported that lovastatin therapy was associated with a significant decline in serum ubiquinol content and that there was an increased oxidizability of LDL in the lovastatin treated patients. In the present study the ubiquinol-10/LDL-cholesterol ratio showed no significant changes.…”
Section: Ubiquinol/ubiquinone Ratio and Antioxidantmentioning
confidence: 99%